시스플라틴 유도 체중감소에 대한 반하사심탕 추출물의 방어효과 - 김하림; 김미성; 이영래; 류도곤; 임찬한; 김병숙; 이금산; 권강범; Kim, Ha Rim; Kim, Mi Seong; Lee, Young Rae; Ryu, Do Gon; et al. (동의생리병리학회지, 2017)
In this study, Banhasasim-tang extracts (BSTE) have an inhibitory effects on cisplatin-induced decrease of body weights in two mouse model. Cisplatin is the most widely used anticancer drug for treatment of various cancer. However, cisplatin treatment to cancer patients leads to many side effects such as nausea, vomiting and body weight decrease. BSTE has been used to decrease digestive disorders in South Korea. We hypothesize that BSTE improve the cisplatin-induced side effects in mouse models. We found that pre- and co-administration of BSTE inhibited decreases of body weights and food intake by cisplatin in mouse models. But BSTE had no synergistic effects for tumor shrinkage by cisplatin in xenograft model. Collectively, our data suggest that BSTE have great potential as a agent for having decrease effects on side effects by cisplatin in cancer patients.